2008
DOI: 10.1103/physrevb.77.165306
|View full text |Cite
|
Sign up to set email alerts
|

Spin polarization in modulation-dopedGaAsquantum wires

Abstract: We study spin polarization in a split-gate quantum wire focusing on the effect of a realistic smooth potential due to remote donors. Electron interaction and spin effects are included within the density functional theory in the local spin density approximation. We find that depending on the electron density, the spin polarization exhibits qualitatively different features. For the case of relatively high electron density, when the Fermi energy E F exceeds a characteristic strength of a long-range impurity poten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…4,5 However, despite much work, both nature and origin of the exchange interaction that drives the spin polarization remains widely debated. Two mechanisms are generally cited in literature: many-body exchange arising from Coulomb interaction at low carrier densities, [6][7][8][9] and the possibility of a Kondo effect by virtual bound states or by localized spins in confined mesoscopic systems. [10][11][12] For the latter case it was suggested that a many-body spin polarization arises from an indirect Ruderman-Kittel-Kasuya-Yosida ͑RKKY͒ exchange, 5 which can be tuned with gate voltage in an oscillatory manner.…”
mentioning
confidence: 99%
“…4,5 However, despite much work, both nature and origin of the exchange interaction that drives the spin polarization remains widely debated. Two mechanisms are generally cited in literature: many-body exchange arising from Coulomb interaction at low carrier densities, [6][7][8][9] and the possibility of a Kondo effect by virtual bound states or by localized spins in confined mesoscopic systems. [10][11][12] For the latter case it was suggested that a many-body spin polarization arises from an indirect Ruderman-Kittel-Kasuya-Yosida ͑RKKY͒ exchange, 5 which can be tuned with gate voltage in an oscillatory manner.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] It was also argued that interaction-induced spontaneous spin splitting can take place in 2DEG systems even in the absence of a magnetic field. [16][17][18] The enhancement of the effective g factor was also observed in carbon-based systems. In graphite the effective g factor is reported to be g * ≈ 2.5.…”
Section: Introductionmentioning
confidence: 63%
“…In Figure 3 A, our predicted E g (D) curves are in agreement with the semiconducting state (symbols) predicted by the DFT method, [26,[55][56][57] but different from the predicted metallic state with E g (D) = 0 eV using the TB method because of the localized state at the Fermi level. [39,41,42] In fact, the met-allic or semiconducting state reported for ZZ-GNRs has also been reflected with some simple sine or cosine functions. The difference in the BOs observed there is ascribed to the role of edge saturation by H, which generates localized edge states by the TB method [41,42] but results in the bandgap expansion by the DFT method.…”
Section: Resultsmentioning
confidence: 91%
“…[39,41,42] In fact, the met-allic or semiconducting state reported for ZZ-GNRs has also been reflected with some simple sine or cosine functions. The difference in the BOs observed there is ascribed to the role of edge saturation by H, which generates localized edge states by the TB method [41,42] but results in the bandgap expansion by the DFT method. [23,43] To see how E m g (D) and E a g (D) contribute to E g (D) of ZZ-GNRs, the functions of E a g (D) and E m g (D) are further plotted in Figure 3 with dashed curves.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation